TINJAUAN HUKUM ISLAM TERHADAP SISTEM KEWARISAN PADA MASYARAKAT BADUY DI INDONESIA - Guspita, Devika Rosa; Sibawaihi, Muhammad (IAIN BONE, 2023)
The background idea for this article arises from the complexity of the Baduy inheritance system which includes elements of custom, tradition and religion in the dynamics of inheritance. Therefore, this article aims to understand how Baduy inheritance law interacts with Islamic law, as well as how changes and adaptations occur in this system. This research methodology uses relevant legal theories, including the Theory of Unwritten Law or Urf theory, the Objectification Theory of Islamic Law by Kuntowijoyo, and Legal Change from Ibn al-Qayyim al-Jauziyah. Data was collected through in-depth interviews with members of the Baduy community, participant observation, and analysis of documents related to positive law and Islamic law. Data were analyzed using an interpretive approach. The research results show that Baduy inheritance law reflects their traditional and religious values, while also interacting with Indonesian positive law in certain respects. The conclusion of this research is that Baduy inheritance law is a real example of legal pluralism in Indonesia. The importance of recognizing and respecting Baduy inheritance law in reviewing Islamic law needs to be considered to maintain cultural and religious diversity in Indonesia.